2015
DOI: 10.4238/2015.september.9.5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and characterization of the Dof gene family in Medicago truncatula

Abstract: ABSTRACT. The DNA-binding one zinc finger (Dof) family is a classic plant-specific zinc-finger transcription factor family, which is involved in many important processes, including seed maturation and germination, plant growth and development, and light responses. Investigation of the Medicago truncatula genome revealed 42 putative Dof genes, each of which holds one Dof domain. These genes were classified into four groups based on phylogenetic analysis, which are similar to the groups reported for Arabidopsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
(41 reference statements)
1
19
0
Order By: Relevance
“…As shown in Supplementary material 1, which illustrates the intron/exon gene structure, the positions and phases of most Dof gene introns are conserved between sorghum and cotton [38]. There are 78 GmDof genes in soybean (genome size 1100 Mb) [39], 34 SlDof genes in tomato (genome size 900 Mb) [40], 76 BraDof genes in Chinese cabbage (genome size 485 Mb) [41], 35 StDof genes in potato (genome size 844 Mb) [42], 42 MtDof genes in Medicago truncatula (genome size 500 Mb) [43], and 46 DcDof genes in carrot (genome size 421.5 Mb) [44], while the number of known GhDof genes in G. hirsutum L. has increased to 114. G. hirsutum L. (AD 1 , 2n = 4x = 52, genome size 2.5 Gb) is an allotetraploid plant species with a D-subgenome and A-subgenome.…”
Section: Ghdof Genes Are Amplified By Segmental Duplicationmentioning
confidence: 99%
“…As shown in Supplementary material 1, which illustrates the intron/exon gene structure, the positions and phases of most Dof gene introns are conserved between sorghum and cotton [38]. There are 78 GmDof genes in soybean (genome size 1100 Mb) [39], 34 SlDof genes in tomato (genome size 900 Mb) [40], 76 BraDof genes in Chinese cabbage (genome size 485 Mb) [41], 35 StDof genes in potato (genome size 844 Mb) [42], 42 MtDof genes in Medicago truncatula (genome size 500 Mb) [43], and 46 DcDof genes in carrot (genome size 421.5 Mb) [44], while the number of known GhDof genes in G. hirsutum L. has increased to 114. G. hirsutum L. (AD 1 , 2n = 4x = 52, genome size 2.5 Gb) is an allotetraploid plant species with a D-subgenome and A-subgenome.…”
Section: Ghdof Genes Are Amplified By Segmental Duplicationmentioning
confidence: 99%
“…Based on genome or transcriptome sequences, a total of 20, 36, 38, 42, 76, and 78 Dof TFs have been identified in Chrysanthemum [17], Arabidopsis [18], pigeon pea [19], Medicago truncatula [20], Chinese cabbage [21], and soybean [22], respectively. Some members of Dof TF family have been extensively studied from a variety of plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, PPT1 gained many new cis-elements at the promoter region 454 (3k bp upstream of the start codon). The function of these cis-elements ranges from 455 elements responsive to light (GT1CONSENSUS (Shu et al, 2015)) to elements 456 controlling tissue specificity (CAATBOX1 (Muthamilarasan et al, 2015)) and elements 457 controlling cell specificity (CACTFTPPCA1 (Akyildiz et al, 2007;Gowik et al, 2004), 458 DOFCOREZM (Yanagisawa, 2000)). Interestingly, all these cis-elements that were 459 predicted to be newly recruited into the promoter of PPT1 during C4 evolution were also 460 predicted to exist in promoters of other genes in the C4 shuttle (including NADP-ME, 461 PEPC, PEPC-k, PPDK and PPDK-RP), H and P subunit of Glycine decarboxylase 462 (Supplemental file 2).…”
Section: Ppt1 From C4 Species Is a Bidirectional Transport Of Pep 395mentioning
confidence: 99%
“…and F. trinervia (C4), using the online tool Plantpan2.0 360 (http://plantpan2.itps.ncku.edu.tw/) with a score threshold of 0.9. We found that both 361 PPT1 and PPT2 recruited new cis-elements at the transition between C3 to C3-C4 stage, 362 e.g., CACTFTPPCA1: a MC specific cis-element detected in PEPC (Akyildiz et al, 363 2007;Gowik et al, 2004); CAATBOX1: a tissue specific enhancer (Muthamilarasan et 364 al., 2015); and GT1CONSENSUS (Shu et al, 2015) and IBOXCORE (Martinez-365 Hernandez et al, 2002), light responsive cis-elements (Table 1, Supplemental file 2). 366…”
mentioning
confidence: 99%